Microbiome and colorectal carcinoma: insights from germ-free and conventional animal models - Tlaskalova-Hogenova, Helena; Vannucci, Luca; Klimesova, Klara; Stepankova, Renata; Krizan, Jiri; Kverka, Miloslav (Cancer journal (Sudbury, Mass.), 2014)
The mammalian microbiota plays a crucial role in the pathogenesis of many diseases. Thanks to recent advances in metagenomics, proteomics, and metabolomics, microbiome composition and metabolic activity can now be studied in detail. Results obtained by such fascinating and provocative studies would be meaningless without considering the perspective of the whole organism. Our work using gnotobiology as the major tool to unravel the mechanisms of host-microbe interaction has demonstrated the crucial role of microbiota in the initiation and progression of inflammation-associated colorectal neoplasia. Carcinogenesis in the gut is driven by the presence of potentially harmful microbes or by lack of protective ones, by the production of carcinogens generated by microbes, and by the induction of inflammation and modulation of the immune system. Here, we review these mechanisms with special emphasis on those where gnotobiology has yielded important insights.
Keywords: Colorectal Neoplasms; Animals; gnotobiologické modely; nádorové mikroprostředí; Humans; kolorektální nádory; Inflammation; mikrobiota; lidé; zánět; Germ-Free Life; zvířata; Tumor Microenvironment; Microbiota; modely nemocí na zvířatech; Disease Models, Animal